Remenant of vitellointestinal duct with vitelline cyst causing volvulus of small bowel - D., Vinodh; S., Maniselvi; Anand V. M., Sabari; R., Kannan (International Surgery Journal, 2022)
We report a case of 14 year old male who presented with abdominal pain for 1 day. Our initial clinical suspicion was complicated acute appendicitis, which was later supported by ultrasonogram. His CT abdomen revealed acute intestinal obstruction. Subsequently he was taken up for emergency laparotomy which revealed a fibrous cord like remnant of vitellointestinal duct with a Vitelline cyst causing volvulus of small bowel. The cord along with cyst was excised. The gangrenous bowel was resected and an ostomy was fashioned. Post operative period uneventful and evaluation for any associated congenital malformations revealed none.